PEMANFAATAN EKOENZIM DARI KULIT BUAH-SAYUR UNTUK PENINGKATAN KUALITAS AIR DANAU BATUR DI KECAMATAN KINTAMANI BANGLI, BALI - Suyasa, I Wayan Budiarsa; Susanah Rita, Wiwik; Irdhawati, Irdhawati; Gede Widihati, Ida Ayu; Wirajana, Nengah; Sibarani, James (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2024)
Eco enzyme production through the fermentation process of household waste, such as leftover fruit and vegetables can also be a solution to minimize waste from its source. This research aims to determine the effect of a mixture of organic materials, fruit and vegetable waste eco enzyme on pH, and the effect of eco enzyme dosage on improving the water quality of Lake Batur, Kintamani Bali. Making eco enzymes using vegetable and fruit waste. water, molasses in a ratio of 3: 10: 1. The liquid is fermented for 3 months while observing the fermentation process. Eco enzyme is harvested and filtered, ready for testing to improve the water quality of Lake Batur. The results of observations of making eco enzyme can be explained that in the first 4 weeks, there was a change in colour with shades of brown to reddish, after the fourth week the colour was relatively stable (no colour change. Changes in pH during the process of making eco enzymes were related to variations in the composition of organic material (vegetable residues. There was a decrease in pH). with an average of up to 1 digit, the highest reduction occurred in ingredients containing papaya, mango and mustard greens. Eco enzymes can improve water quality as indicated by several water quality parameters, but are not enough to achieve conformity with the established quality standards. Keyword: Eco Enzyme; Water Quality; Batur Lake